Strategy Development as A Driver of Business Sustainability Based on Swot Analysis From The Perspective of Islamic Economics in The MSME Sector - Sari, Dian; Devy Wulandari; Rizky Amaliyah Ramdhani Ilham; Andi Abdul Gaffar; Murtiadi Awaluddin; Sudirman (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
The micro, small and medium enterprise (MSME) sector is considered as the main driver of economic growth and as a temporary place for workers who have not been absorbed in the formal sector. In maintaining the existence of a business, it is necessary to conduct a study of the strengths, weaknesses, opportunities, and threats that occur when the business is carried out. SWOT analysis is basically a technique for systematically identifying various factors and determining elements of the development of an institution. This study uses a qualitative approach that focuses on literature studies, where researchers do not conduct field research and rely on data sources from literature. This study takes sources from articles, books, magazines, the articles we take are articles related to the research theme for at least the last 5 years. After the SWOT analysis is carried out, strategies can be developed by utilizing the SWOT matrix, which consists of four types of strategies: SO (Strengths-Opportunities), WO (Weaknesses-Opportunities), ST (Strengths-Threats), and WT (Weaknesses-Threats). SWOT analysis compares external factors of opportunities and threats with internal factors of strengths and weaknesses. Structured external and internal testing is something unique in planning and development. SWOT analysis is carried out using the results of identifying internal and external conditions of an institution or company. These results are identifications from the internal and external sides, so it is necessary to prepare a strategy presented in the form of a matrix with four strategy options. Along with the development of the era, SWOT analysis is not only used in the industrial world, companies or an organization. However, it can also be used as self-control in order to make a person better. Therefore, this study will discuss the use of SWOT analysis to control daily life from an Islamic economic perspective. So that a plan for an institution or organization will emerge that is in accordance with the standards of Islamic economic principles.